2010
DOI: 10.1371/journal.pone.0011293
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Trends of the Pharyngeal Dentition in Cypriniformes (Actinopterygii: Ostariophysi)

Abstract: BackgroundThe fish order Cypriniformes is one of the most diverse ray-finned fish groups in the world with more than 3000 recognized species. Cypriniformes are characterized by a striking distribution of their dentition: namely the absence of oral teeth and presence of pharyngeal teeth on the last gill arch (fifth ceratobranchial). Despite this limited localisation, the diversity of tooth patterns in Cypriniformes is astonishing. Here we provide a further description of this diversity using X-ray microtomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 58 publications
2
54
1
Order By: Relevance
“…Microtomography provides high-resolution three-dimensional reconstructions of mineralized tissues [22,26], allowing the virtual segmentation and investigation of both pharyngeal bones and teeth, but not the KCP. Thus, it was possible to scrutinize the number and arrangement of pharyngeal teeth, as well as individual shape of tooth crowns.…”
Section: Results (A) Phylogeny Of the Cyprininaementioning
confidence: 99%
See 2 more Smart Citations
“…Microtomography provides high-resolution three-dimensional reconstructions of mineralized tissues [22,26], allowing the virtual segmentation and investigation of both pharyngeal bones and teeth, but not the KCP. Thus, it was possible to scrutinize the number and arrangement of pharyngeal teeth, as well as individual shape of tooth crowns.…”
Section: Results (A) Phylogeny Of the Cyprininaementioning
confidence: 99%
“…Right and left sets of pharyngeal teeth do not interlock but together occlude against a keratinized chewing pad (KCP) that covers the pharyngeal plate of the basioccipital [21]. Across the order, there is great diversity in the arrangement, number and shape of pharyngeal teeth [22]. Some species have one row encompassing numerous teeth while others have three rows with fewer teeth on each row.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the short and broad pharyngeal bones, while bearing molar teeth, are good at dealing with invertebrates (e.g., insects and mollusks); the intermediate pharyngeal bones and diverse morphotypes of teeth (conical, coarsely compressed and extremely compressed) are adapted to a large variety of foods including both algae and aquatic insects; and the long and narrow pharyngeal bones usually bearing extremely compressed teeth are suited for herbal diets (e.g., algae and plant debris) (Eastman, 1977;Sibbing, 1982Sibbing, , 1991aLiem & Sanderson, 1986;Zeng & Liu, 2009). While the contribution of pharyngeal bones to diversification of cichlids and their evolutionary process has been documented in detail (Liem & Sanderson, 1986;Hulsey, 2006), studies on evolutionary pattern and process of pharyngeal bones and teeth in cyprinids are scarce (Pasco-Viel et al, 2010). It has been suggested that cyprinid pharyngeal bones and teeth may bear important systematic value.…”
Section: Introductionmentioning
confidence: 99%
“…The terminology and the morphotypes for the fish pharyngeal teeth follow Nakajima (1984), Böhme (2002) and Pasco-Viel et al (2010). The right half tooth formulae are presented whenever needed.…”
Section: Methodsmentioning
confidence: 99%